The informative and persuasive functions of advertising: A moral appraisal — A further comment - Lee, Kam-Hon (Journal of business ethics, 1987)
This paper argues that product and advertisement are neither completely dependent nor completely independent. The advertisement of a bad product cannot be good. The advertisement of a good product is not necessarily good. In the case where consumer sovereignty cannot be assumed, the goodness of an advertisement depends solely on the goodness of the product. In the case where consumer sovereignty can be assumed, the goodness of an advertisement depends first on whether the product is good, and if so, whether the advertisement preserves individual autonomy.